Debt, hedging, and human capital - Stephen D. Smith; Larry D. Wall (Federal Reserve Bank of Atlanta, 2005)
This paper provides a theory of debt and hedging based on human capital. We distinguish human capital from physical capital in two ways: (1) human capital is inalienable and can exercise a one-sided option to leave the firm, and (2) human capital is not perfectly replaceable. We show that a firm may reach the first best solution while issuing debt or equity to outsiders provided that either the insiders receive a senior claim or that the firm hedges. We then show that, given asymmetric information concerning costs, the only viable solution has the firm issuing debt to outsiders and hedging.
Keywords: 330; Humankapital; Hedging; Kapitalstruktur; Börsengang; Theorie